2022
DOI: 10.3390/su141811168
|View full text |Cite
|
Sign up to set email alerts
|

Government Ownership and Corporate Cash Holdings: Empirical Evidence from the Amman Stock Exchange

Abstract: While the effect of ownership structure on the level of cash holdings has been widely examined, that of government ownership has been understudied. Using a generalized method of moments (GMM) estimation on the panel data of 107 Jordanian firms listed on the Amman Stock Exchange, this research adds to the limited literature on the relationship between government ownership and the level of corporate cash holdings. Consistent with agency theory, the findings reveal that firms with government ownership hold higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…From the regression results in Table 6, it can be seen that the ordinary OLS regression did not test the significant influence of the potential characteristics of the supervisory board on irregularities. Using the Heckman two-step test, model (5) found that IMR was significantly negatively correlated with the number of violations at the 10% confidence level, validating the hypothesis that the model had sample selection bias, at this time, the Structural characteristics has a significant positive correlation with the number of irregularities at the 5% level, and the other three characteristics have no significant impact on irregularities. After adding more variables to models ( 6) and (7), almost all of them have no significant effect on the dependent variable.…”
Section: Robustness Testmentioning
confidence: 59%
See 1 more Smart Citation
“…From the regression results in Table 6, it can be seen that the ordinary OLS regression did not test the significant influence of the potential characteristics of the supervisory board on irregularities. Using the Heckman two-step test, model (5) found that IMR was significantly negatively correlated with the number of violations at the 10% confidence level, validating the hypothesis that the model had sample selection bias, at this time, the Structural characteristics has a significant positive correlation with the number of irregularities at the 5% level, and the other three characteristics have no significant impact on irregularities. After adding more variables to models ( 6) and (7), almost all of them have no significant effect on the dependent variable.…”
Section: Robustness Testmentioning
confidence: 59%
“…There are many reasons for the appearance and occurrence of irregularities and violations, and the research on them is also a complex system. Current studies contribute to irregularities of listed companies have covered many factors, perspectives and levels, such as the structure of the board of directors [2][3][4][5] , independent directors [3,6] , executive compensation structure [7,8] , executive background characteristics [9,10] , ownership structure [11][12][13] , the shareholding ratio of institutional investors [14] , external auditors [15][16][17] , asset quality [18] , etc.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…For example, family-controlled firms prefer more discretion over the firm resources to enable them to pursue their family interests (Chrisman et al 2013); hence, they are likely to avoid lines of credit, their attached covenants, and subsequent monitoring. The incentive of Jordanian firms to increase discretion over firm resources and avoid bank monitoring is not surprising given that the controlling family holds large ownership stakes (Alkhataybeh et al 2022) and actively participates in the management of the firm (Tayem et al 2019). In addition, Jordanian firms operate in an economy with low investor protection, and hence there is a large scope for controlling shareholders to derive substantial private benefits of control at the expense of other investors (Tayem et al 2019).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…We consider cash flow as the driver of cash hoarding. Some scholars have noted an inverse link between cash flow and cash hoarding (Al-Najjar, 2015;Gill & Shah, 2012), but others have found a positive link between cash flow and cash hoarding (Al-Khataybeh et al, 2022;Drobetz & Gruninger, 2007). Tayem (2017) finds a positive association between cash flow and cash hoarding according to the pecking order theory, revealing that companies choose internal sources of financing over external ones.…”
Section: Cash Flow and Cash Hoardingmentioning
confidence: 99%